Broadband Plasmonic Logic Input Sources Constructed With Dual Square Ring Resonators and Dual Waveguides - Jing Wen; Jiannong Chen; Kang Wang; Bo Dai; Yuanshen Huang; Dawei Zhang (IEEE Photonics Journal, 2016)
We propose a broadband plasmonic logic source, which is a nanostructure composed of two parallel plasmonic gap waveguides coupled with dual square ring resonators aligned in a vertical or horizontal manner. The numerical simulations show that this configuration has up to 3-bit logic combinations for three output ports when the input port is illuminated with the combination of white sources and different wavelength filters. The three output ports of this plasmonic nanostructure can be used as the broadband illuminating sources for three input logic gates, such as the and gate or the or gate.